Fermented food products in the era of globalization: tradition meets biotechnology innovations. (August 2021) - Galimberti, Andrea; Bruno, Antonia; Agostinetto, Giulia; Casiraghi, Maurizio; Guzzetti, Lorenzo; Labra, Massimo
Graphical abstract: Highlights: Fermented food is strongly connected with the territory of origin and tradition. Multi-omics profiling unveils the microbial signature of food typicalities. Machine learning and data mining are crucial to harness fermentation processes. Biotechnology can fill the gap between traditional and industrial fermentation. Preserving local functional microbial consortia guarantees global food security. Abstract : Omics tools offer the opportunity to characterize and trace traditional and industrial fermented foods. Bioinformatics, through machine learning, and other advanced statistical approaches, are able to disentangle fermentation processes and to predict the evolution and metabolic outcomes of a food microbial ecosystem. By assembling microbial artificial consortia, the biotechnological advances will also be able to enhance the nutritional value and organoleptics characteristics of fermented food, preserving, at the same time, the potential of autochthonous microbial consortia and metabolic pathways, which are difficult to reproduce. Preserving the traditional methods contributes to protecting the hidden value of local biodiversity, and exploits its potential in industrial processes with the final aim of guaranteeing food security and safety, even in developing countries.